Luminescence temperature anti-quenching in CdSe/CdS core/shell and CdSe/CdS/ZnS core/double shell nanostructures - Linh, Nguyen Dieu; Lieu, Nguyen Thi Thuy; Hien, Nguyen Thi Minh; Nghia, Nguyen Xuan (Vietnam Journal of Science and Technology, 2022)
Luminescence temperature anti-quenching (LTAQ) was investigated on CdSe/CdS core/shell and CdSe/CdS/ZnS core/double shell nanostructures prepared by hot injection method. They have the same core size, CdS shell thickness ranging from 1 to 5 monolayer (ML) and ZnS shell thickness of 2 ML. Temperature-dependent photoluminescence (PL) spectra of the purified core, core/shell, and core/double shell samples were comparatively investigated over a temperature range of 79 - 460 K. The LTAQ phenomenon was observed for the core/shell and core/double shell nanostructures and is reversible. The fluorescence recovery magnitude and the temperature range in which the LTAQ process occurs depends on the thickness and composition of the shell surrounding the core. Analysis of the temperature-dependent spectral characteristics shows an increase in compression strain in the CdSe core when increasing the shell thickness. The cause of the LTAQ phenomenon is attributed to the rearrangement of the atoms at the core/shell and shell/shell interfaces in the investigated nanostructures due to thermal expansions of the core and shell crystalline lattices. The linear dependence of integrated emission intensities of CdSe/CdS (1 ML) and CdSe/CdS (3 ML) samples on temperature in the ranges of 220 - 360 K and 270 - 340 K, respectively, opens up the prospect of creating temperature sensors for biomedical applications.